Implementation of a validated post-operative opioid nomogram into clinical gynecologic surgery practice: A quality improvement initiative - Nicole C. Zanolli; Stephanie Lim; William Knechtle; Kelvin Feng; Tracy Truong; Laura J. Havrileskey; Brittany A. Davidson (Elsevier, 2023)
Objectives: The Gynecologic Oncology Postoperative Opioid use Predictive (GO-POP) calculator is a validated tool to provide evidence-based guidance on post-operative opioid prescribing. The objective of this study was to evaluate the impact of the implementation of GO-POP within an academic Gynecologic Oncology division. Methods: Two cohorts of patients (pre-implementation and post-implementation) who underwent surgery were compared with reference to GO-POP calculator implementation. All patients were included in the post-implementation group, regardless of GO-POP calculator use. An additional expanded-implementation cohort was used to compare pain control between GO-POP users and non-GO-POP users prospectively. Wilcoxon rank sum tests or ANOVA for continuous variables and Chi-square or Fisher's exact tests were used to categorical variables. Results: The median number of pills prescribed post-operatively decreased from 15 pills (Q1: 10, Q3: 20) to 10 pills (Q1: 8, Q3: 14.8) after implementation (p < 0.001). In the expanded-implementation cohort (293 patients), 41% patients were prescribed opioids using the GO-POP calculator. An overall median of 10 pills were prescribed with no difference by GO-POP calculator use (p = 0.26). Within the expanded-implementation cohort, refill requests (5% vs 9.2%; p = 0.26), clinician visits (0.8% vs 0.6%, p = 1), ED or urgent care visits (0% vs 2.3%, p = 0.15) and readmissions (0% vs 1.7%, p = 0.27) for pain did not differ between those prescribed opioids with and without the GO-POP calculator. Conclusions: A 33% reduction in post-operative opioid pills prescribed was seen following implementation of the GO-POP calculator into the Gynecologic Oncology division without increasing post-operative pain metrics or encounters for refill requests.